2016
DOI: 10.5935/1678-9741.20160034
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve prolapse in pregnancy

Abstract: Mitral valve prolapse is a benign condition. Mitral regurgitation is only complicated in patients with severe mitral valve prolapse. Women with mitral valve prolapse in the absence of other cardiovascular disorders tolerate pregnancy well and do not develop remarkable cardiac complications. Nevertheless, serious complications of mitral valve prolapse, including arrhythmia, infective endocarditis and cerebral ischemic events, can be present in pregnancy. Debates remain with regard to the use of prophylactic ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…There has not been a previous study that has evaluated the influence of gender in the association between MVP and KCN. However, there are several studies that have demonstrated an association between MVP and women of childbearing age [ 31 , 32 , 33 ]. Yuan et al reported that cardiac problems in pregnant women, especially MVP, are a topic of concern [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has not been a previous study that has evaluated the influence of gender in the association between MVP and KCN. However, there are several studies that have demonstrated an association between MVP and women of childbearing age [ 31 , 32 , 33 ]. Yuan et al reported that cardiac problems in pregnant women, especially MVP, are a topic of concern [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, primary mitral valve prolapse (MVP) due to myxomatous valve disease is the most common valvular disease in pregnancy ( 41 ). MVP is usually suspected or diagnosed with clinical findings of systolic click and mitral regurgitant murmur, but these findings may not be classical in pregnancy because of the volume increases and lower systemic resistance that occur in pregnancy ( 42 , 43 ). The diagnosis is confirmed and the severity of mitral regurgitation ascertained by echocardiography ( Figure 3 ).…”
Section: Mitral Valve Disordersmentioning
confidence: 99%
“…Asymptomatic women with mitral valve prolapse and chronic, severe regurgitation usually tolerate pregnancy without significant complication although the increased cardiac volume may be associated with signs and symptoms of volume overload and atrial fibrillation. This can generally be managed with careful diuresis and beta blockers ( 16 , 42 , 44 ). Metoprolol can be safely used in pregnancy but may be associated with fetal bradycardia so should be used judiciously.…”
Section: Mitral Valve Disordersmentioning
confidence: 99%